Preparation and characterization of pH dependent κ-carrageenan-chitosan nanoparticle as potential slow release delivery carrier - Yew, H.C.; Misran, M. (Springer Verlag (Germany), 2016)
A polymeric carrier has high potential as active ingredient delivery vehicle owing to its biocompatibility and biodegradability. In this work, pH dependency of the oppositely charged polymers in forming nanoparticle was investigated. A positively charged chitosan and a negatively charged κ-carrageenan were mixed at varied mass ratios (v/v) with a pH ranged from 3 to 6, respectively, to form nanoparticles through polyelectrolyte complexation. The main interest of this research, is to evaluate the effect of pH on the formation of stable active ingredients encapsulated nanoparticle for sustained release. Based on the FTIR result, the presence of new absorption band at 1584 cm−1 and slight shift in the spectrum, indicated the complexation of the polymers. The Zetasizer’s measurements showed that irrespective to the combination of chitosan and κ-carrageenan, increase in pH solution decreased the size and the zeta potential of the nanoparticles. Furthermore, depending on the combinations, the yield and the swelling percentage of the nanoparticle could reached up to 80 and 200%, respectively. Among the mass ratio combinations, the ratio 1:1 at pH 4 had the best physical properties. The encapsulation efficiency of the κ-carrageenan-chitosan nanoparticles exhibited higher preference towards more water soluble active ingredients, ascorbic acid as compared to caffeine and lidocaine. In addition, the slow release of active ingredients from the κ-carrageenan-chitosan nanoparticles, is plausibly due to the electrostatic interaction and compactness of the nanoparticles. Thus, they might be suitable for prolonged release applications.